Major Directions in Populism Studies: Is There Room for Culture? - Aslanidis, Paris (PARTECIPAZIONE E CONFLITTO, 2020)
The article highlights the absence of a cultural dimension in the academic literature of populism and advocates in favor of studying grassroots social movements as the primary milieu where culture interacts with populist mobilization. Beginning with an original classification of existing schools of thought on populism that uses the historical figure of William Jennings Bryan as a conceptual yardstick, it moves on to lay out a framework for cultural analysis through the lens of collective action frame theory, based on an understanding of populism as a discursive mode of political identification.